THE APPLICATION OF JOB SAFETY ANALYSIS (JSA) METHOD IN IDENTIFYING THE RISK OF WORK ACCIDENTS IN CHARGED MANPOWER IN BUNGKUTOKO PORT, KENDARI CITY: Job Safety Analysis - Samma, Muh. Yamin; Deden Miftah, Erwin Azizi Jayadipraja; Abd. Azis Harun (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: Data from the Ministry of Manpower of the Republic of Indonesia that the number of work accidents in Indonesia in 2016 was 101,368, in 2017 there were 123,041 cases, in 2018 there were 173,415 cases. At the end of September 2019 there were 130,923 cases and there were 6 people who died every day. On September 2019, the sectors that contributed to the relatively large number of work accidents were the processing industry with 50,358 (38.46%) cases, trade of 9,559 (7.30%) cases, transportation and warehousing 2,694 (2.06%) cases, and the rest 68,312 (52.18%) cases from other sectors. The same thing was reported by the Social Security Administration for Employment that there was an increase in work accidents by 40%, from 157,313 in 2018 to 173,105 cases in 2019. Methods: This research is quantitative research with a descriptive analytic research design and applied observational analytic approach. The population of all loading and unloading workers was 150 people divi ded into 3 teams, where each team consisted of 50 TKBM members of Bungkutoko Port, Kendari City. Result: This study found 3 work stages with the highest RPN value, namely, wrong in the lifting position in the stevedore of work process at the time workers lift goods and put them into the net, as well as in the cargodore Â of work process when workers stack goods on the truck with a value of 288, stumbling (cargo) which occurs in the stevedoring work process where The worker on the truck directs the crane and the net into the truck body with an RPN value of 192, and pinched by a lifting tool in the cargodore of work process when workers remove goods from the sling on the truck / remove the sling, with a value of RPN 144. Conclusion: There were 3 loading and unloading work processes, namely, stevedoring, cargodoring, and delivery with each work stage having potential hazards, the impact of hazards, and control efforts, and the person in charge of control efforts.